Hal Ashby and the making of Harold and Maude - Davidson, James A. 1958- (McFarland & Company, Inc., Publishers, 2016)
"The original script was sold to a major Hollywood studio virtually overnight. The film flopped upon release and later became one of the great cult successes of all time. This is the story of the making of Harold and Maude, shot in the San Francisco Bay Area in the winter of 1971"...